2019
DOI: 10.1002/jlb.5hi1018-392rr
|View full text |Cite
|
Sign up to set email alerts
|

Frontline Science: Low regulatory T cells predict perioperative major adverse cardiovascular and cerebrovascular events after noncardiac surgery

Abstract: Immune cells drive atherosclerotic lesion progression and plaque destabilization. Coronary heart disease patients undergoing noncardiac surgery are at risk for perioperative major adverse cardiac and cerebrovascular events (MACCE). It is unclear whether differential leukocyte subpopulations contribute to perioperative MACCE and thereby could aid identification of patients prone to perioperative cardiovascular events. First, we performed a hypothesis-generating post hoc analysis of the LeukoCAPE-1 study (n = 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 55 publications
3
27
0
Order By: Relevance
“…Therefore, numbers cannot be compared to histological findings in this cohort. However, our previous results (17) in connection with the current findings lead to the intriguing hypothesis that there is a connection between circulating Tregs, plaque stability and patients' outcome after surgery. Oxidative stress increases Treg apoptosis in a high fat mouse model (40) rendering this also a possible mechanism explaining the lower Treg numbers in the plaques under perioperative stress from 2nd surgery.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Therefore, numbers cannot be compared to histological findings in this cohort. However, our previous results (17) in connection with the current findings lead to the intriguing hypothesis that there is a connection between circulating Tregs, plaque stability and patients' outcome after surgery. Oxidative stress increases Treg apoptosis in a high fat mouse model (40) rendering this also a possible mechanism explaining the lower Treg numbers in the plaques under perioperative stress from 2nd surgery.…”
Section: Discussionsupporting
confidence: 81%
“…Low numbers of circulating Tregs are associated with atherosclerosis (39). Additionally, we have recently shown that preoperative low counts of Tregs are associated with cardiac adverse events after non-cardiac surgery (17). When looking at the atherosclerotic lesion itself, low numbers of Tregs within the plaque have been associated with plaque vulnerability (15,37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies described by Scholz et al . in this issue of the Journal of Leukocyte Biology have significantly advanced our knowledge on MACCE following major noncardiac surgery, in particular the potential importance of silent cardiovascular disease (vulnerable asymptomatic atherosclerotic plaques) and the significance of Tregs.…”
mentioning
confidence: 96%
“…). Importantly, Scholz et al . also provide important information on the Treg cell counts at which such effects become clinically significant.…”
mentioning
confidence: 99%